2017
DOI: 10.1080/15402002.2016.1266490
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of the Insomnia Severity Index in Veterans With History of Traumatic Brain Injury

Abstract: Objective/Background The Insomnia Severity Index (ISI) is a widely used self-report measure of insomnia symptoms, however to date this measure has not been validated or well-characterized in Veterans who have experienced traumatic brain injury (TBI). This study assessed the psychometric properties and convergent, divergent, construct, and discriminate validity of the ISI in Veterans with a history of TBI. Participants Eighty-three Veterans with history of TBI seen in the VA San Diego Healthcare System as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
1
40
0
1
Order By: Relevance
“…14,15 Although the initial development of the ISI did not include factor structure examination, numerous investigators have reported distinct differences in the structure of the ISI across samples. Two studies, one in a sample of veterans with traumatic brain injury 12 and the second in a community sample of 230 older adults, 10 supported a single-factor structure for the ISI. In contrast, Savard, Savard, and Ivers revealed a twofactor structure of the ISI in a large sample of French-speaking cancer patients, with the first four items loading onto Factor I and the last three loading onto Factor II 8 (see Table 3).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…14,15 Although the initial development of the ISI did not include factor structure examination, numerous investigators have reported distinct differences in the structure of the ISI across samples. Two studies, one in a sample of veterans with traumatic brain injury 12 and the second in a community sample of 230 older adults, 10 supported a single-factor structure for the ISI. In contrast, Savard, Savard, and Ivers revealed a twofactor structure of the ISI in a large sample of French-speaking cancer patients, with the first four items loading onto Factor I and the last three loading onto Factor II 8 (see Table 3).…”
Section: Introductionmentioning
confidence: 96%
“…For example, an internet‐delivered intervention for insomnia revealed the ISI had low internal consistency at baseline (α = .61), but good internal consistency post‐intervention (α = .88). Furthermore, although a study of sleep clinic participants demonstrated acceptable internal consistency (α = .74), a study of cancer patients (α = .90) and another of veterans with traumatic brain injury both reported excellent internal consistency, (α = .90 and α = 0.92, respectively). Of note, the prior study of cancer patients used a mixed sample, composed of participants who were both, on and off treatment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, previous studies have revealed that TBI patients have increased wake after sleep onset (WASO) and decreased sleep efficiency. 11,41,42 Most studies also find that total sleep time during nocturnal sleep is reduced and sleep latency is increased in TBI subjects. 7 The only prospective and controlled electrophysiological study to date demonstrates that sleep is more consolidated after TBI, and there is a trend toward increased slow-wave activity.…”
Section: Tbi Effects On Clinical Sleep Parametersmentioning
confidence: 99%
“…These, together with the Insomnia Severity Index, are the only three questionnaires to be validated in TBI populations. 41,72,73 Differentiating fatigue (physical or cognitive tiredness that does not result in sleep) and sleepiness (tiredness that leads to sleep) can be challenging, and it remains unclear if it is worthwhile when assessing patients for TBI-SWD. Recently, fatigue improvement was shown to correlate with subjective TBI-SWD improvement.…”
Section: Tbi-swd Screeningmentioning
confidence: 99%